Multi-physiology modeling of the immune system in the era of precision immunotherapy - Hong, Sunghyun; Park, Kyemyung (Frontiers in Immunology, 2025)
Immunotherapies using new modalities, including antibody-based drugs, nanoparticle-delivered drugs, and adoptive cell therapy, have become major treatment options for immune-related diseases such as cancer, autoimmune diseases, and infections. Although data characterizing individual patients’ pharmacological responses, immune statuses, and clinical outcomes become increasingly available, predicting individual patients’ immunotherapeutic responses for developing and deploying optimal immunotherapies remains challenging. Here, we propose “multi-physiology modeling” of the immune system that integrates omics-based and dynamic systems modeling-based systems immunology and pharmacometrics modeling on top of basic and clinical immunology. The multi-physiology modeling approach aims to integrate different physiological systems to realistically simulate the multi-scale and complex interactions of the immune system under intervention by immunotherapeutic agents for predictive immunotherapies tailored to individual patients. This will accelerate not only our understanding of basic immunology related to immune-related diseases but also the efficiency and accuracy of clinical immunotherapeutics in the era of precision immunotherapy.